MIGRATION, MSMEs AND ECONOMIC DEVELOPMENT IN NIGERIA - UCHEGBULAM, JOACHIN CHETACHI; OKORONKWO, SCHOLASTICA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study investigates the impact of migration on sustainable economic development in Nigeria, with a particular focus on the effects on the growth and sustenance of Micro, Small and Medium Enterprises (MSMEs). The motivation for this research stems from the need to address the brain drain and labor loss, arising from migration, as well as its implications for Nigeria’s economy. In recent years, the mass migration of Nigerian youths has raised concerns about its effects on the emergence and sustainability of MSME businesses, which are essential drivers of economic growth in the country. This study utilizes a combination of qualitative and quantitative research methods, to analyze data from within the last 10 years, on migration trends and MSME establishment and growth in Nigeria. The data is sourced from secondary sources such as; the National Bureau of Statistics, Macrotrends and Moniepoint. Descriptive and inferential statistical analyses were employed, in order to identify the impact of migration patterns on MSMEs establishment and sustenance in Nigeria. The study found a moderate positive correlation between net migration and the number of active MSME businesses in Nigeria, as the correlation level of 0.372 is not statistically significant, at a 0.05 level of significance. This study contributes to the existing literature on economic development, technological change and growth, particularly in relation to human resources, human development, income distribution, and migration.